File Carving Survey on Techniques, Tools and Areas of Use - Alrobieh, Ziad Saif; Raqpan, Ali Mohammed Abdullah Ali (Discoveries in Agriculture and Food Sciences, 2020)
In digital and computer forensics, file carving is a very hot research topic. That is the main reason why the research is needed to be focused on improving file carving techniques, so that digital investigation can obtain important data and evidence from damaged or corrupted storage media. In the digital forensic investigation, analyzing the unallocated space of storage media is necessary to extract the deleted or pre-written files when the file system metadata is missing or corrupted. Data carving can be defined as a method to recover the file from unallocated space based on different factors such as file type, information of the file (Header/Footer), or the contents of the file. Research in this area focuses on technological improvements in terms of tools and techniques over the past years. The studies examine different techniques of data carving, especially multimedia files (eg. images and videos). The work file carving is classified into three categories classic carving techniques, intelligent carving techniques and smart carving techniques. Moreover, there are seven popular multimedia carving tools that are mostly used and experimentally evaluated are presented. We conclude that proposing new advanced method for carving multimedia files still open and new direction for future research. This is because the fragmentations and compression are very commons used and useful for these kind of files.